2022
DOI: 10.15252/embr.202154281
|View full text |Cite
|
Sign up to set email alerts
|

Cyprinid‐specific duplicated membrane TLR5 senses dsRNA as functional homodimeric receptors

Abstract: Membrane‐embedded Toll‐like receptor 5 (TLR5) functions as a homodimer to detect bacterial flagellin. Cyprinid grass carp (Ctenopharyngodon idella) encodes two TLR5 genes, CiTLR5a and CiTLR5b. Here, we show that cyprinid TLR5a and TLR5b homodimers unexpectedly bind the dsRNA analog poly(I:C) and regulate interferon (IFN) response in early endosomes and lysosomes. Although TLR5 homodimers also bind flagellin, an immune response to flagellin is only triggered by TLR5a/b heterodimer. Moreover, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…After A. hydrophila infection, overexpression of CiTLR5Ma and CiTLR5Mb genes were observed in immune system tissues and vital organs, including the liver, spleen, and head kidney, suggestive of their important roles in the immune response to the invasion of pathogens. Moreover, CiTLR5Ma and CiTLR5Mb showed similar expression patterns across tissues, which supports the finding that CiTLR5Ma and CiTLR5Mb are subfunctionalized to sense bacterial flagellin as a heterodimer (Liao et al, 2022).…”
Section: Figuresupporting
confidence: 84%
See 2 more Smart Citations
“…After A. hydrophila infection, overexpression of CiTLR5Ma and CiTLR5Mb genes were observed in immune system tissues and vital organs, including the liver, spleen, and head kidney, suggestive of their important roles in the immune response to the invasion of pathogens. Moreover, CiTLR5Ma and CiTLR5Mb showed similar expression patterns across tissues, which supports the finding that CiTLR5Ma and CiTLR5Mb are subfunctionalized to sense bacterial flagellin as a heterodimer (Liao et al, 2022).…”
Section: Figuresupporting
confidence: 84%
“…Frontiers in Genetics frontiersin.org soluble members of the M/S type play a synergistic role in sensing flagellin (Tsujita et al, 2004) possibly implying that soluble TLR5 is redundant in function and disappears in some fish and endothermic vertebrates. Cyprinid-specific duplicated membrane TLR5 (M/M type) demonstrated neofunctionalization to sense viral dsRNA as functional homodimeric receptors in antagonistic effect (Liao et al, 2022). Domain number variation was identified in the fish TLR5 isotypes, generating functional diversity and complexity (Asami and FIGURE 4 The expression patterns of CiTLR5Ma and CiTLR5Mb on transcription level in tissues of liver, spleen and head kidney, after infected with A.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Teleost fish have undergone whole genome duplication and grass carp encodes two tandem TLR5 genes, CiTLR5a and CiTLR5b . Liao et al ( 2022 ) started by comparing the sensitivity of the two CiTLR5 paralogs to different MAMPs. Various flagellins or flagellated bacteria were sensed by CiTLR5a and CiTLR5b heterodimers for activation of NF‐κB, a transcription factor regulating the expression of pro‐inflammatory genes in both fish and mammals.…”
mentioning
confidence: 99%
“…In mammals, TLR3 is specialized in sensing viral dsRNA (Liu et al, 2008), while TLR5 recognizes the MAMP flagellin (Yoon et al, 2012;Fig 1). The well-established notion of TLR5 as a purely "bacterial" flagellin TLR has now been challenged by Liao et al in this issue of EMBO Reports (Liao et al, 2022) Notably, the CiTLR5 ectodomains directly bound poly(I:C). Through a comprehensive series of domain swaps and mutagenesis, the authors showed that flagellin recognition requires canonical TLR5 recognition sites in both CiTLR5a and CiTLR5b.…”
mentioning
confidence: 99%